The Contribution of Students' Language Attitude toward The Success of English Learning in An Indonesian Islamic Boarding School - Nafisah, Nahdia Ilma; Anugerahwati, Mirjam; Karmina, Sari (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2025)
Students’ language attitude is one aspect that contributes to the output of learning (Garret,  2010). The study aims to investigate the contribution of students' language attitudes towards the success of English learning. The research setting is in an Islamic boarding school in Indonesia. Under a qualitative research method and a case study design, students' interviews are conducted to collect the data. The data are descriptively analyzed using thematic analysis. The finding reveals that students with a positive attitude towards English have high motivation for learning English and vice versa. The success of learning English is indicated by the higher English scores and academic achievements, like winning English competitions. Therefore, the study suggests that teachers build the students' positive attitude towards English to acquire successful English learning.